The Diagnostic Value of Plasma Copeptin Level in Patients with Acute Appendicitis - Gurger, Mehtap; Telo, Selda (Clin Lab Publ, 2022)
Background: This study aims to determine the effectiveness of plasma copeptin level, leukocyte, and neutrophil-tolymphocyte ratio (NLR) in the diagnosis of patients with acute appendicitis presenting to the emergency department. Methods: Patients over the age of 18 presenting to the emergency department due to abdominal pain and diagnosed with acute appendicitis as a result of clinical, laboratory, and radiological evaluation were included in the study. The control group consisted of healthy volunteers. Blood samples were taken from all groups at the time of admission. Plasma copeptin level was studied using the ELISA kit. Statistical Package for the Social Sciences v.22 (IBM SPSS Statistics for Windows; IBM Corp., Armonk, NY, USA) was used for statistical analysis. Results: Fifty patients and 50 healthy volunteers were included in the study. Plasma copeptin, leukocytes, and NLR levels were found to be significantly higher in the appendicitis group compared to the control group. In receiver operating characteristic curve (ROC) analysis, copeptin had 96% sensitivity and 92% specificity at the optimal cutoff value of 3.2 ng/mL to predict patients with appendicitis [area under the curve (AUC): 0.994, 95% confidence interval (CI): 0.984 - 1, p < 0.0001)]. Conclusions: In this study, plasma copeptin levels, leukocytes, and NLR were found to be significantly higher in AA patients compared to healthy volunteers. Increased plasma copeptin level in AA patients may play a potential role in the diagnosis of appendicitis.
Keywords: appendicitis; copeptin; diagnosis